Deciphering the mechanism behind efficient enantioselective ethylation with thiazolidine‐based amino alcohols. (30th December 2021) - Tavares, Nélia C. T.; Cacho, Vanessa R. G.; Costa, Dora C. S.; Nunes, Sandra C. C.; Pais, Alberto A. C. C.; Murtinho, Dina; Silva Serra, M. Elisa
Abstract : Taking advantage of the opposite chirality of two privileged starting materials, l ‐cysteine and d ‐penicillamine, a wide range of thiazolidine‐based amino alcohols was synthesized. l ‐Cysteine derivatives were more efficient chiral inductors than the d ‐penicillamine ones, with ee up to 92% in the enantioselective ethylation of benzaldehyde. The scope of the best catalyst was evaluated using several aromatic, heteroaromatic, and aliphatic aldehydes, providing excellent ( S )‐enantioselectivities. Given the opposite chirality of the l ‐cysteine and d ‐penicillamine thiazolidines, it was expected that the use of one or the other type of derivative as ligand would allow the formation of opposite configurations of the alkylated product. However, whereas the l ‐cysteine thiazolidines predominantly gave the ( S ) form of the alkylated product, the d ‐penicillamine ones led to both configurations. The significant difference in the stereochemical outcome of this reaction when catalyzed by the two types of ligands prompted us to investigate the reasons behind such results. Extensive quantum chemical calculations were performed in order to identify the transition state structures by which the enantioselective ethylation of benzaldehyde in the presence of these type of amino alcohols can proceed. An alternative path for the rate‐determining step was also explored and found decisive for the rationalization of the experimental outcomes. It was observed that the type of ligand dictates the accessible reaction paths for the formation of the chiral product, which ultimately determine the balance between the two possible configurations. Abstract : Optically active l ‐cysteine and d ‐penicillamine‐based thiazolidines were prepared, and their chiral induction was evaluated in the enantioselective alkylation of aldehydes, with ee up to 93% ( S ). Quantum chemical calculations were performed in order to rationalize the stereochemical outcome of the catalytic reaction, namely, the differences in enantioselectivity displayed by the l ‐cysteine and d ‐penicillamine ligands. The complete set of located transition state structures allowed to rationalize the observed enantioselectivities and to identify the available mechanistic paths for each type of ligand.